The prevalence and awareness of menopausal symptoms among perimenopausal and postmenopausal women visiting a tertiary care hospital - Sachdeva, Priyanka; Sengar, Mahima; Kalra, Ruchi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: The growing number of postmenopausal women has important implications for healthcare systems, as these women may face specific health concerns associated with menopause and ageing. The study aimed to know the prevalence and awareness of menopausal symptoms among perimenopausal and postmenopausal women visiting tertiary hospitals. Methods: A cross-sectional design was used for data collection and analysis. Women aged 45 years and above in the perimenopausal and postmenopausal age groups were included. We utilised the menopausal rating scale questionnaire as a tool. Results: A maximum percentage of women (73%) reported physical and mental exhaustion, bladder problems (66%), joint and muscular discomfort (61%), and irritability (59.66%). Additionally, 46.6% of women reported having hot flushes. Dryness of the vagina in 41.33%. Among the 45 to 55 years age maximum women had hot flushes (60.71%), the sexual problem (54.83%), irritability (54.74%), and depressive mood (32%). Among 56 to 65 years age the most common complaints were sleep disturbance (58.62%), bladder problems (45.96%), Anxiety (44.58%), physical and mental discomfort (40.63%), joint and muscular discomfort (39.89%), and vaginal dryness (36.29%). Among the 66 to 75 the heart discomfort was highest (45.67%). Among women aged 76 years and above, age depressive symptoms (16%) and sleep problems (13.79%) were present. Conclusions: There is a high prevalence of menopausal symptoms and a lack of awareness among women, implying a need for healthcare initiatives in India, where this issue receives little attention. We strongly advocate a governmental policy for menopausal women to support their specific health needs.